Pemanfaatan Kulit Pisang dan Daun Gamal sebagai Bahan Baku Mikroorganisme Lokal: Sosialisasi dan Pelatihan - Fany Juliarti Panjaitan; Onesimus Ke Lele; Rizki Adiputra Taopan; Angela Asista Asti; Fransisuks Vani; Evaldus Hambur (Institut Pertanian Bogor, 2023)
Local Microorganisms (MOL) is a type of organic fertilizer that is environmentally friendly, inexpensive and easy to produce independently. The hope is that MOL can support organic farming so that farmers can produce agricultural products that are safe and healthy for consumption. MOL is known to have a variety of multipurpose microorganisms and is rich in nutrients. Therefore, this information is important to be disseminated to the millennial generation on various occasions including Community Service activities carried out by lecturers at universities. The target of this activity is the students of the public school, Vocational High School (VHS) 2 Kota Komba, which is located in East Manggarai Regency, East Nusa Tenggara Province. This activity aims to provide students with an understanding of the importance of environmentally friendly agriculture by utilizing forage and household waste as raw materials for making MOL and how to make it independently. The implementation of this activity is in the form of socialization and training. The socialization was carried out to provide theoretical knowledge to partners about the benefits and advantages obtained from MOL, then continued with training and direct assistance in making it involving 22 students. The training was conducted by dividing participants into 4 working groups (5‒6 people/group). The process of making MOL is carried out according to the work procedures that have been prepared. The results of the socialization, training and mentoring activities for making MOLs can add new insights and knowledge and form work skills for partners in making MOLs. This is shown by the active participation of the students in discussions and enthusiasm in the process of making MOL until it is successful.